Dual PI3K and HDAC inhibitor, CUDC-907, effectively inhibits endometrial cancer growth in vitro and in vivo - Zhang, Xudong; Lazaro-Camp, Vanessa; Li, Tianyue; Qi, Amanda; Lan, Lingyun; Lamont, Lillie; Zhao, Lu; Meehan, Maggie R.; Gardner, Sophia N.; Meng, Wendy; Xiong, Yiqin; Leidinger, Mariah; et al. (Frontiers in Oncology, 2025)
PurposeHyperactivation of the PI3K/AKT/mTOR pathway promotes tumor progression in many cancers. Among these, endometrial cancer (EC) exhibits the highest frequency of alterations in this pathway, making it an ideal model for targeted treatment. Progestin therapy is initially effective, but advanced EC often resists treatment due to loss of progesterone receptor (PR) and acquired resistance. Furthermore, as obesity is the main etiological driver of EC, obesity-related factors activate the PI3K/AKT pathway and inhibit PR function. Therefore, there is a clinical need to identify therapies that enhance progestin sensitivity by upregulating PR, downregulating obesity-related factors, and inhibiting the PI3K/AKT pathway.MethodsA dual HDAC (histone deacetylase) and PI3K inhibitor, CUDC-907 (fimepinostat), was tested for its ability to inhibit the proliferation of endometrial cancer cells both in vitro and in vivo by targeting PI3K and HDAC pathways. A WST-1 Cell Proliferation Colorimetric Assay Kit was used to assess cell viability. Western blotting was used for protein expression. Endometrial cancer xenograft models were established in mice fed a high-fat-diet, normal chow, or subjected to fasting to evaluate the drug’s activity under different metabolic conditions. Serum biomarkers were quantified using enzyme-linked immunosorbent assay (ELISA).ResultsRapid inhibition of the PI3K/AKT pathway was observed; CUDC-907 treatment downregulated p-AKT, p-rS6, and p-4EBP1. Concurrently, transcriptional inhibition of HDAC activity was also observed. PR expression was restored, downstream genes FOXO1, p21, and H3Ace were upregulated, and oncogenes Myc and HER2 (Neu/ErbB2) were downregulated. CUDC-907 induced both intrinsic and extrinsic apoptotic pathways. In vivo, CUDC-907 inhibited EC progression, increased survival of tumor-bearing mice, and suppressed tumor growth. Notably, CUDC-907 was most effective in reducing tumor growth in mice on high-fat diets. Furthermore, serum IGF-1 levels decreased following CUDC-907 treatment, suggesting that IGF-1 may serve as a surrogate serum marker for the CUDC-907 drug’s effect in EC.ConclusionOur findings suggest that CUDC-907 is a promising agent that can re-sensitize tumors to progestin therapy and improve outcomes for EC patients. This study supports CUDC-907 as a potent treatment strategy in endometrial cancer and identifies IGF-1 as a potential surrogate serum biomarker for therapeutic response.